Implementation of Stunting Prevention Program in Indonesia: Literature Review - Feny Ditya Hanifah; Syahrizal (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: The health problem of stunting is still a crucial problem in various regions of the world. The reduction of stunting is one of the goals of the Sustainable Development Goal (SDG) target where in 2030 the expected target is 89 million people, but in fact, there is no maximum progress in achieving the World Health Assembly (WHA) global nutrition target in 2025. Various studies have been conducted out there that provide comprehensive facts related to various kinds of programs or methods in reducing the prevalence of stunting that can be taken into consideration by the government in making new policies related to stunting prevention. Objective: This study aims to identify the various implementations of stunting prevention interventions in Indonesia. Method: The research method uses a scoping review with the PRISMA approach. Literature research through three databases, namely PubMed, ScienceDirect, and Scopus. The inclusion criteria for this study were articles published from 2017 to 2023, articles that had free access and full text, research locations in Indonesia, and not systematic review and/or meta-analysis articles. Result: The search results obtained 13 final articles that discuss variations in interventions in stunting prevention. The results of the review of 13 articles found that effective prevention of stunting can be done by various methods, such as providing education, counseling, therapeutic group therapy, practical demonstrations, and home visits through professional collaboration between health workers and health cadres to pregnant women and mothers with children less than five years old, as well as premarital education classes for prospective couples. Conclusion: Implementation of effective stunting prevention interventions should be multisectoral and include family planning, premarital couples, and women with early pregnancies as the main target focus for stunting prevention.